Reading Comprehension, Second Edition: Strategies for Independent Learners - Harvard Business School Publishing Corporation (The Guilford Press, 2008)
"This book is essential reading for those who are new to teaching or who want to enhance their comprehension instruction. The user-friendly format allows teachers to read the book from cover to cover or to sample individual chapters based on interests or needs. From strategies for reading fiction and nonfiction to ideas for engaging in research and other learning tasks, Blachowicz and Ogle’s informative work is packed with useful explanations, techniques, and tips for helping students become better comprehenders. Based on extensive work with teachers and students in schools, this practical book deserves a special place on any literacy educator’s bookshelf."--Rachel Brown, PhD, Reading and Language Arts Center, Syracuse University